2022
DOI: 10.1007/s11218-021-09684-1
|View full text |Cite
|
Sign up to set email alerts
|

Bullies, victims, and meanies: the role of child and classmate social and emotional competencies

Abstract: This study used a personal oriented approach to identify distinct combinations of children’s experiences of bullying and victimisation in the Irish primary school context. The study investigated the social and emotional characteristics that predicted those profiles at individual and classroom levels. The sample of 2,062 participants was drawn from the Irish national cohort study Children’s School Lives. We analysed teacher reports of individual children’s strengths and difficulties and neglect, and child repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…The phenomenon of bullying in Indonesia is an important issue, in addition to the trend which is still high, the concept of strengthening character education in Indonesia also does not agree with this phenomenon (Fitriyah et al, 2022). Some studies indicated that bullying had been studied extensively (Soori, Rezapour, & Khodakarim, 2014;Han et al, 2017;Sari & Yendi, 2019;D'Urso et al, 2022, Borowiec et al, 2021. We had observed that the victims of bullying were dominantly teenagers than adults.…”
Section: Discussionmentioning
confidence: 92%
“…The phenomenon of bullying in Indonesia is an important issue, in addition to the trend which is still high, the concept of strengthening character education in Indonesia also does not agree with this phenomenon (Fitriyah et al, 2022). Some studies indicated that bullying had been studied extensively (Soori, Rezapour, & Khodakarim, 2014;Han et al, 2017;Sari & Yendi, 2019;D'Urso et al, 2022, Borowiec et al, 2021. We had observed that the victims of bullying were dominantly teenagers than adults.…”
Section: Discussionmentioning
confidence: 92%
“…However, it is essential to consider that the phenomenon of victimization and its effects on peer relationships may also be cyclical. For instance, D'Urso et al (2022) found that caring peers in classrooms played a vital protective role in whether a child was victimized. This suggests that positive peer relationships can break the cycle of victimization and foster a supportive environment for adolescents prone to victimization; likely, a similar effect could be possible also in cybervictimization.…”
Section: Discussionmentioning
confidence: 99%
“…Our VR game and provocative scenario are based on [60], and measures of emotional reactions in studies with children were taken using SAM scales [37]. Furthermore, there is a class of interventions proven to work in schools and to reduce cyberbullying in social media [17,23,48,54], from which we base our interventions. Additionally, the presence of visible authority figures and parental involvement can affect the effectiveness of interventions [9,14,21,32,58].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that children paired with a mentor experienced less peer victimisation. Within classrooms, having classmates who showed more peer support and who were older in general than children in other classrooms, reduced the risk of being a victim of bullying [23]. Indeed, it was shown that peers act as a group to influence the development of individual children [22].…”
Section: Bullying and Cyberbullying Prevention And Interventionmentioning
confidence: 99%